The Islamic Bloc at the United Nations Human Rights Council - Rist, Duncan Graham (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2020)
Uncertainty as to the future of the liberal international order and the position of the United States within an international system in which it is not the hegemon remains a topic of debate amongst scholars of International Relations (Acharya: 2017; Duncombe and Dunne: 2018; Ikenberry: 2009, 2011, 2014; Nye: 2012 and Monteiro: 2011/2012). Fukuyama's (1989: 4) "end of history" has not happened and a resurgence of populist leaders within established liberal democratic countries has contributed to a rapid decline of moral and ethical leadership and has further compromised the future of the liberal international order (Duncombe and Dunne, 2018: 27). As the relative power of the United States declines and the future of the liberal international order becomes increasingly uncertain, support for its future must be sought from outside the West (Duncombe and Dunne, 2018: 25 and Ikenberry: 2009). This thesis seeks to locate where potential non-Western support for the future liberal international order may be found. It does so through an analysis of how Islamic states who are part of the Organisation of Islamic Cooperation vote on the United Nations Human Rights Council (UNHRC). The OIC has a significant presence at the UNHRC and can influence the direction of the liberal international human rights regime. The evidence examined in this research project suggests that the future liberal international order and human rights regime can indeed expect some form of cooperation from the OIC. However, the OIC, and by extension Islamic states, would likely offer more support at least for human rights, if a more common understanding were to be found.
Keywords: United Nations Human Rights Council; Organisation of Islamic Cooperation; International relations; International relations -- Moral and ethical aspects; Political leadership -- Moral and ethical aspects; Power (Social sciences) -- United States; Human rights -- International cooperation; Liberalism -- International cooperation